2011
DOI: 10.1186/1465-9921-12-139
|View full text |Cite
|
Sign up to set email alerts
|

Activated MCTC mast cells infiltrate diseased lung areas in cystic fibrosis and idiopathic pulmonary fibrosis

Abstract: BackgroundAlthough mast cells are regarded as important regulators of inflammation and tissue remodelling, their role in cystic fibrosis (CF) and idiopathic pulmonary fibrosis (IPF) has remained less studied. This study investigates the densities and phenotypes of mast cell populations in multiple lung compartments from patients with CF, IPF and never smoking controls.MethodsSmall airways, pulmonary vessels, and lung parenchyma were subjected to detailed immunohistochemical analyses using lungs from patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 48 publications
9
80
1
1
Order By: Relevance
“…This result is consistent with previous studies that also found increased mast cells14–16 and their TGF-β1-positive phenotype in IPF lungs 15. Our decellularised lung experiments also showed that mouse BMMC or rat PMCs were activated while reseeded in fibrotic matrix as shown by an increase in the secretion of active and total TGF-β1.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with previous studies that also found increased mast cells14–16 and their TGF-β1-positive phenotype in IPF lungs 15. Our decellularised lung experiments also showed that mouse BMMC or rat PMCs were activated while reseeded in fibrotic matrix as shown by an increase in the secretion of active and total TGF-β1.…”
Section: Discussionsupporting
confidence: 93%
“…An increase of mast cells has been reported in the airways of patients with IPF (48,49), and the density of mast cells was recently shown to be higher in IPF lung than in other fibrotic lung disease (50). Interestingly, patients with IPF that had a high mast cell density had a higher degree of fibrosis, and the number of mast cells correlated negatively with patient lung function (51). We compared the microarray time course expression data in the bleomycin model with microarray data from human IPF biopsies to identify molecular markers with translational relevance, and demonstrated that the highest similarity of gene expression between bleomycin-induced lung fibrosis and IPF in animals occurs at 7 days after bleomycin administration.…”
Section: Original Researchmentioning
confidence: 94%
“…Of note, IL-1a processing activity is readily detected in the bronchoalveolar lavage fluids from patients with cystic fibrosis or bronchiectasis (Afonina et al, 2011). In addition to neutrophils, emerging evidence points to an important role for mast cells in pulmonary fibrosis (Andersson et al, 2011;Overed-Sayer et al, 2013). Importantly, Pseudomonas aeruginosa, a common respiratory pathogen in cystic fibrosis, has been reported to upregulate IL-1a and IL-1b in mast cells, further facilitating neutrophil transendothelial migration (Lin et al, 2002).…”
Section: Il-1amentioning
confidence: 97%